Estudo morfoanatômico e químico de Microlicia hatschbachii Wurdak (Melastomataceae) - Cassiano, Dayse Santos Almeida (2010)
Microlicia hatschbachii Wurdack belongs to Melastomataceae family,Microlicieae trib. Studies about anatomical and chemical features of Microlicia genus are scarce. This work aimed to describe morpho-anatomy of leaves and stem and to study chemical composition of external constituents of leaf (wax and glandular exudates) and hexane extract of aereal parts of M. hatschbachii. The analysis of wax and glandular exudates was obtained by GC-MS and HPLC-DAD, respectively. The hexane extracts was fractionated by column chromatography using silica gel and the compounds obtained were analyzed by GC-MS. The species has elliptic to oval-elliptic leaves, entire margin, acute apex and rounded symmetrical base. The leaf blade is amphistomatical with anisocytic and anomocytic stomata, the epidermis is unisseriate with isodiametric cells and several glandular trichomes. The mesophyll is isobilateral with bicollateral vascular bundles surrounded by some sclerenchymatic cells. The stem has unisseriated epidermis and bicollateral vascular organization. There are phenolic compounds in epidermical cells and several prisms of calcium oxalate were found in leaves, peciole and stem. Gas chromatographymass spectrometry of the wax shown presence of alkanes and diterpenoids and the analysis of glandular exudates by HPLC-DAD shown the presence of a flavonoid and benzene derivatives. From hexane extract of aereal parts of M. hatschbachii were identified aliphatic alkanes, methyl esters of long chain acids, carboxylic acids and it were isolated for the first time in Melastomataceae the diterpenoids labd 8(17)-en-15-oic acid and labd-8(17),13-dien-15-oic acid. These diterpenoids were identified by 1H and 13C NMR and 2D NMR (COSY, HMQC, HMBC) and other compounds were characterized by GC-MS.